Knowledge and attitude of tobacco use and cessation among dental professionals - Awan, K.H. (Saudi Dent J, 2015)
AIM: Smoking is the one of the most preventable causes of death worldwide. Dental professionals may play an important role in anti-smoking campaigns. The aim of this study was to evaluate current knowledge of and attitudes toward smoking and its cessation among dental professionals. MATERIALS AND METHODS: This questionnaire-based study was carried out among general dental practitioners (GDPs) and dental students in Saudi Arabia. The questionnaire was used to collect data on sociodemographic characteristics, knowledge, and attitudes toward tobacco use and cessation. Data were analyzed using SPSS software (version 18.0; IBM) and the Mann–Whitney U-test, with a significance level of p < 0.001. RESULTS: A total of 342 participants (130 GDPs, 212 dental students) with the mean age of 24 (standard deviation, 5) years participated in the study. One-third (33.8%, n = 44) of GDPs and 30.2% (n = 64) of dental students were smokers; small percentages (GDPs, 9.1% [n = 4]; dental students, 7.8% [n = 5]) were heavy smokers. The majority of participants rated both smoking cessation and prevention together as a very important preventive measure. Families were rated as the most important factor responsible for smoking cessation, whereas general practitioners were rated as the most important factor for providing assistance with cessation. CONCLUSION: More meaningful participation of dental professionals in tobacco cessation is needed, with implications for related curriculum changes.